2009
DOI: 10.1007/s12098-009-0252-5
|View full text |Cite
|
Sign up to set email alerts
|

Even a single third trimester antenatal fetal screening for congenital anomalies can be life saving

Abstract: We report two cases of malrotation with extremely different outcomes based on the availability and non-availability of antenatal scanning. The first one had a single third trimester ultrasound which detected malrotation and helped in saving baby's life whereas the second baby without antenatal screening succumbed to midgut volvulus and its sequelae because of delayed presentation. In developing countries where most of the pregnancies may go unsupervised, a single third trimester scan for fetal anomalies by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…Ultrasound can contribute considerably to diagnosis and treatment of ectopic pregnancy and abortion as well as complications later in pregnancy (Rogo 2004; Sy et al. 2009; Bawa & Kannan 2010). Harris and Marks (2009) described the coincidental reduction in maternal mortality in Nicaragua from 12% to 5% with the implementation of ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound can contribute considerably to diagnosis and treatment of ectopic pregnancy and abortion as well as complications later in pregnancy (Rogo 2004; Sy et al. 2009; Bawa & Kannan 2010). Harris and Marks (2009) described the coincidental reduction in maternal mortality in Nicaragua from 12% to 5% with the implementation of ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Seffah and Adanu (2009) attributed this to the high fertility rate in most developing countries and the popularity of having an ultrasound performed during pregnancy. Ultrasound can contribute considerably to diagnosis and treatment of ectopic pregnancy and abortion as well as complications later in pregnancy (Rogo 2004;Sy et al 2009;Bawa & Kannan 2010). Harris and Marks (2009) described the coincidental reduction in maternal mortality in Nicaragua from 12% to 5% with the implementation of ultrasound.…”
Section: Ultrasound In Obstetrics and Gynaecologymentioning
confidence: 99%
“…Currently, the American College of Obstetricians and Gynecologists and the American College of Radiology recommend routine sonograms in the first and/ or second trimester, but state that no evidence exists to recommend routine sonograms in the third trimester [14]. Bawa and Kannan demonstrated different outcomes of fetal intestinal volvulus based on the performance of prenatal scanning, and suggested that a single third trimester scan for fetal anomalies may be an effective strategy to reduce perinatal mortality [15]. We believe that patients with fetal bowel dilatation should be closely followed in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Molvarec et al reported two cases of fetal intestinal volvulus, which were delivered promptly on the basis of ultrasound findings and biophysical monitoring of the fetus 23. Bawa and Kannan demonstrate different outcomes of fetal intestinal volvulus based on the performance of prenatal scanning; one fetus identified with dilated bowel underwent prompt surgical intervention and survived, whereas another succumbed with the postnatal diagnosis of volvulus when no prenatal sonogram was performed 24. They suggested that a single third trimester scan for fetal anomalies may be an effective strategy to reduce perinatal mortality 24…”
Section: Discussionmentioning
confidence: 99%